Fitness aerobics as a means of recovery the physical capacity of young volleyball players (boys and girls) - Kozina, Z.; Cretu, M.; Boichuk, Y.; Sobko, I.; Repko, O.; Bazilyuk, T.; Prokopenko, I.; Tararak, N.; Osiptsov, A.; Guba, A.; Trubchaninov, M.; Kostiukevych, V.; et al. (Trends in Sport Sciences, 2018)
mproving the results in sports involves applying loads with significant volumes and intensity. It requires the introduction into the system of preparation of a complex of recovery the physical capacity. The study put forward the hypothesis that the use of fitness aerobics as a means of recovery will positively affect the level of functional capabilities, general and special physical fitness of volleyball players 16-17 years old. Aim of Study. The purpose of the work is to experimentally substantiate the use of fitness with elements of aerobics asa means of recovery physical performance in the training process of volleyball players of 16-17 years (boys and girls). Material and Methods. The study involved athletes engaged in volleyball at The Dvorichansky youth and children`s club of physical training "Youth" of the Kharkiv region, in the number of 30 boys and 30 girls (age 16-17 years). Both teams are silver winners of the championship of the Kharkiv region volleyball season 2016--2017 years. The study was conducted from September 2016 to May 2017. During nine months during the regenerative periods, athletes were engaged in fitness with elements of aerobics with a fitness trainer. Duration of lessons was 40 minutes. Lessons were held 2 times a week in the last week of each month. Results.It is established that it is advisable to organize muscular activity, taking into account its directed influence on the body, that involves management of physical capacity and recovery processes. It has been shown that for athletes of 16-17 years of age, it is necessary to use special recovery cycles with a wide inclusion of recovery means with the transition to other types of physical exercises. The effectiveness of the dosed monthly application of aerobics as a means of restoring the efficiency of young volleyball players is substantiated. The developed method positively influences both girls and boys. However, under the influence of the developed technique, the girls improve their recovery. This can be explained by the fact that girls are more emotional, so the use of aerobics with music has a more significant impact on on their body. Conclusion. Conducting fitness classes with elements of aerobics in the training process of young volleyball players helps to recovery physical performance, increases the level of physical fitness and improves the functionality of athletes. The developed method positively influences both girls and boys. Under the influence of the developed technique, the girls improve their recovery.